Contributions and future perspectives on the use of magnetic nanoparticles as diagnostic and therapeutic tools in the field of regenerative medicine - Santo, Vítor E. (2013)
The current limitations of regenerative medicine strategies may be overcome through the use of magnetic nanoparticles (MNPs), a class of nanomaterial typically composed of magnetic elements that can be manipulated under the influence of an external magnetic field. Cell engineering approaches following the internalization of these MNPs by cells and/or the incorporation of these nanosystems within 3D constructs (scaffolds or hydrogels) may constitute a new attractive approach to achieve a magnetically responsive system enabling remote control over tissueengineered constructs in an in vivo scenario. Moreover, the incorporation of bioactive factors within these MNPs also enables a targeted and smart delivery of biomolecules to specific regions and/or triggering specific cell responses upon external magnetic stimulation. Certainly, one of the most attractive properties of MNPs is their ability to be used as theranostic tools for regenerative medicine applications, enabling live monitoring and tracking of the system while simultaneously acting as a therapeutic stimulation.